The Effect of Earnings Management and Leverage on Tax Aggressiveness in Manufacturing Companies in the Industrial Sector Listed on the Indonesia Stock Exchange in 2020–2024 - Mulyawati, Lilis; Bayyinah, Delyra Thaif; Sa'adah, Indana Zulfa; Febriyanti, Merlin; Rafifah, Anjelita Dhia; Aprila, Reni; Mahwiyah, Mahwiyah (Jurnal Multidisiplin Sahombu, 2025)
This study aims to examine the effect of earnings management and leverage on tax aggressiveness in manufacturing companies listed on the Indonesia Stock Exchange during the 2020–2024 period. Tax aggressiveness has become a widespread practice, potentially harming state revenue, particularly when firms engage in tax planning strategies through earnings manipulation and debt structuring. The study employs a quantitative approach with panel data regression using purposive sampling of 35 manufacturing firms that consistently reported positive profits and complete financial statements. Tax aggressiveness is measured using the abnormal book-tax difference (AbBTD), while earnings management and leverage are treated as independent variables. The findings show that both earnings management and leverage have a positive and statistically significant effect on tax aggressiveness, both individually and jointly. These results support agency theory, suggesting that managers may act opportunistically to reduce tax burdens. The study recommends enhancing ethical financial reporting practices and strengthening regulatory oversight to minimize tax avoidance behavior.